2014
DOI: 10.1016/j.abb.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Updates of reactive oxygen species in melanoma etiology and progression

Abstract: Reactive oxygen species (ROS) play crucial roles in all aspects of melanoma development, however, the source of ROS is not well defined. In this review we summarize recent advancement in this rapidly developing field. The cellular ROS pool in melanocytes can be derived from mitochondria, melanosomes, NADPH oxidase (NOX) family enzymes, and uncoupling of nitric oxide synthase (NOS). Current evidence suggests that Nox1, Nox4 and Nox5 are expressed in melanocytic lineage. While there is no difference in Nox1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 133 publications
7
95
0
2
Order By: Relevance
“…Our study also documented an increase of ROS in MM tissues and cells. It is reported that melanoma is a ROS‐driven tumor, and ROS played important roles in all aspects of melanoma development . Cancer cells including melanoma cells were reported to show high levels of ROS .…”
Section: Discussionsupporting
confidence: 60%
“…Our study also documented an increase of ROS in MM tissues and cells. It is reported that melanoma is a ROS‐driven tumor, and ROS played important roles in all aspects of melanoma development . Cancer cells including melanoma cells were reported to show high levels of ROS .…”
Section: Discussionsupporting
confidence: 60%
“…Much recent research has focused on how low levels of intracellular ROS (10‐100 nM) regulate tumor growth by facilitating mutagenesis, tumor initiation, and tumor promotion . Members of the NAPDH oxidase (NOX) family play a major role in generating ROS in a broad range of cell types . This 7‐membered family is comprised of NOXes 1‐5 and DUOX 1 and 2 proteins that function to generate ROS by oxidizing NADPH to NADP + .…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the normal redox balance by deregulation in AOS proteins, such as superoxide dismutase (SOD), catalase and glutathione and thioredoxin system proteins, was associated with cancer development [1013]. Dysfunction of ROS-producing systems coevolves with the AOS to a new redox balance leading to the progression from melanocytes to melanoma [14]. Besides, the prooxidant state in melanoma may also induce alterations in proteins involved either in melanogenesis or metastasis.…”
Section: Introductionmentioning
confidence: 99%